PENENTUAN KADAR TOTAL PADATAN TERSUSPENSI PADA AIR ASAM TAMBANG BATUBARA DI KABUPATEN LAHAT MENGGUNAKAN METODE GRAVIMETRI - Adawiyah, Shela; Permata Sari, Suci (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research is entitled Determination of Total Suspended Solids Levels in Coal Mine Acid Water in Lahat Regency Using the Gravimetric Method. The purpose of the study was to determine the determination of total suspended solids content in acidic coal mine water in Lahat Regency using the gravimetric method. The research analysis method is carried out in accordance with SNI 6989.3: 2019 on how to test Total Suspended Solids gravimetrically. The results showed that total suspended solids cause turbidity in water due to undissolved solids and cannot immediately settle, to determine the level of total suspended solids in coal mine acid water, the gravimetric method was used with the results of research at PT.X, PT.Y, and PT.Z not exceeding the quality standards of coal mine acid water where the maximum level is 400 mg/L